Implementation of STEM-EDP Approach Based on SDGs to Improve Critical Thinking Skills (Topic: Global Warming) - Sulau Irlamaida; Shelly Efwinda; Muliati Syam; Abdul Hakim; Lambang Subagiyo; Nurul Fitriyah Sulaeman (Universitas Lambung Mangkurat, 2026)
Thinking critically is essential in the 21st century to solve complex global problems. However, students’ lack of critical thinking skills regarding real-world issues such as global warming needs to be addressed. This study examines the increase in students' critical thinking using STEM-EDP based on the Sustainable Development Goals (SDGs) in global warming materials. Conducted at one of the senior high schools in Samarinda, this study used a group pretest-posttest design with 35 students in class X. The validity instrument used was deemed appropriate by science education experts, and its reliability coefficient was 0.75. Data were collected through critical-thinking tests before and after treatment and analyzed using N-Gain and paired t-tests. Results show STEM-EDP improves critical thinking: the average pretest was 33.10, increasing to 61.92 in the posttest. The N-Gain value of 0.43 is moderate, with the highest increase in hypothesis testing. The paired t-test shows a Sig. of 0.000 (<0.05), indicating a significant difference between the pretest and the posttest. In conclusion, STEM-EDP improves students' critical thinking skills on global warming material. However, posttest scores indicate that skills remain adequate, underscoring the need for further evaluation and improvement of STEM-EDP implementation. The findings of this study can serve as a basis for further investigation by other researchers into which STEM-EDP steps have the greatest impact on critical thinking.